Mathematics Critical Thinking Ability Reviewing from Gender and Independent Learning Students in Stem Problem-Based Learning Assisted by Web E Learning School - Makhmudah, Siti; Suyitno, Hardi; Rusilowati, Ani (Unnes Journal of Mathematics Education Research, 2021)
This study aims to describe students' mathematical critical thinking skills in PBL STEM learning classes in terms of learning independence and gender. This study uses a mixed method (mixed method) sequential explanatory design. This design is combination research, characterized by data collection and quantitative data analysis in the first stage, followed by qualitative data collection and analysis in the second stage. The research subjects were students of class X SMA Negeri 1 Demak. Based on the results of the study, it was found that the mathematical critical thinking skills of male and female students with high learning independence were very good with good verbal skills, mathematical critical thinking skills of male and female students with moderate learning independence with sufficient verbal abilities, thinking skills critical mathematics of male and female students with low learning independence is sufficient with less verbal ability.